2020
DOI: 10.3390/polym12102367
|View full text |Cite
|
Sign up to set email alerts
|

FRP Confinement of Stone Samples after Real Fire Exposure

Abstract: The mechanical properties of stone materials can be severely affected by exposure to high temperatures. The effect of fire on stone buildings could cause irreversible damage and make it necessary to retrofit the affected elements. Particularly, the strengthening of columns by confinement with composites has been widely improved during the last decades. Today, fiber reinforced polymer (FRP) confinement represents a very interesting alternative to traditional steel solutions. This work studied the behavior of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…(iii) Then, the fabric was attached with a 60 mm overlap (25% of the contour length approx. ), which had been found to be sufficient in previous studies [11,13,17] (Fig. 3(c)).…”
Section: Experimental Program and Test Set-upsupporting
confidence: 63%
See 2 more Smart Citations
“…(iii) Then, the fabric was attached with a 60 mm overlap (25% of the contour length approx. ), which had been found to be sufficient in previous studies [11,13,17] (Fig. 3(c)).…”
Section: Experimental Program and Test Set-upsupporting
confidence: 63%
“…Finally, sets 01, 04 and 07 were not heated at all in order to act as control samples. The target temperature was selected on the basis of previous studies [1,17], as it has been proven that this rock exhibits a dramatic loss of physical and mechanical properties at 600 • C. Several tests had been carried out previously, measuring with thermocouples the air temperature in the oven as well as inside some specimens, which allowed small corrections to be made with respect to the theoretical heating curve programmed in the device [28]. Regarding the behavior of the heated samples, it is important to highlight that no spalling or fractures were observed, as opposed to a previous work with real fire exposure [17], where some samples were severely damaged, especially in the quick water-cooled sets.…”
Section: Experimental Program and Test Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, panels formed by two layers of solid ceramic bricks and continuous reinforcements with glass or carbon fiber mesh, applied on both sides, are used. An exposure target temperature of 600 • C is adopted, which is chosen for two main reasons: (i) it is the usual temperature range that can occur during a fire inside a building with stone or masonry walls [49,50]; (ii) it has been shown that the mechanical capacity of the TRMs used is seriously compromised at this temperature level [48], which is why it is considered appropriate to evaluate the capacity of the reinforcements under these conditions. For the application of the TRMs, different scenarios are considered, so that the reinforcements are placed both after the exposure of the walls to 600 • C (i.e., panels with undamaged TRM) or before (elevated temperatures affecting both TRM reinforcement and masonry element).…”
Section: Introductionmentioning
confidence: 99%